Perbaikan Tata Letak Fasilitas Produksi Seal Radiator Menggunakan From to Chart di PT. XYZ - Aldo, Ewaldo; Saufik Lutfianto; Kusuma, Yudha Adi (Metode : Jurnal Teknik Industri, 2025)
The fierce competition of the global industry, operational efficiency is crucial for a company's competitiveness, and optimal facility layout can reduce production costs and accelerate cycle times. From-to charts are used to evaluate and optimise material or product flow. The From-To-Chart method is a traditional way to review and improve material or product flow. Its primary focus is to identify and measure material movement within the factory work area. Based on an initial analysis of the radiator seal production flow at PT. XYZ, efficiency remains low. Initial forward efficiency stands at 74.25%, below the optimal target of 75%. Meanwhile, backward efficiency reaches 25.75%, indicating significant unnecessary and repetitive material movement. This situation arises because certain areas, such as the laboratory and NMI zone, are visited more than once during a single production cycle. The analysis results show an improvement from 74.25% to 98.01%. Its primary function is to identify and calculate material movement moments within the industrial layout, thereby enhancing efficiency and effectiveness during operational time.